The universal service provision (USP) in rural libraries: an exploration study on the usage and problems among underserved communities in Kedah / Nor Azlina Azmi...[et al.] - Azmi, Nor Azlina; Abdul Rahman, Firdaus; Mohamed Sawal, Mohd Zool Hilmie (2011)
Malaysia through its government has proved to world that over the past decade they have been doing a massive development on their information and communications technology (JCT) and to show that the effort has been paid off, we can see the digital divide among Malaysians has now alleviated. Ministry of Energy, Communications and Multimedia (MECM), seeing the rise of JCT in Malaysia has taken a step in introduce Universal Service Provision (USP) program under the Ninth Malaysia Plan. With a cost of RMI billion, the purpose of this project are to improvise basic communications facilities and Internet access to the underserved areas such as schools, health clinics, community centers and libraries. Under the Ninth Malaysia Plan 2006-2010, the second thrust of the National Mission is to seek the enhancement of knowledge, creativity and innovation, in addition to nurture a 'first class mentality' among Malaysian. This 'first class mentality' has been defined as a knowledgeable society. A knowledgeable society means that the Malaysian is able to be competitive, develop an outstanding work culture, as well as honesty and integrity along with moral strength. (Ninth Malaysia Plan, 2006). Despite the noble efforts of the USP project has been long established in several rural libraries around Malaysia but research on its use in rural libraries in Kedah, especially in the vicinity of Merbok yet to be implemented. Therefore, this paper tries to explore and it is hoped it will be reveals the issues related to the problems, the advantages and usability of the tools and facilities USP project. With the implementation of USP projects, it is belief that the service of rural libraries will upgrade towards bridging and educating the rural communities. In addition, the project will create awareness among the rural communities on the importance of JCT, and expose the rural community with K-economy. Therefore, the focus of this research is to investigate the use of USP tools and facilities in rural libraries. Aspects to be studied is from the perspective of the problems faced by rural communities when using these USP tools and facilities, and what do they do with this service being offered to them (usage). With this research, it is hoped it can be used as a guide to the key parties involved in making project USP which among them are rural libraries, government and researchers who wish to pursue research in this field.